Atovaquone Nanosuspensions Show Excellent Therapeutic Effect in a New Murine Model of Reactivated Toxoplasmosis - Schöler, Nadja (American Society for Microbiology, 2001)
Immunocompromised patients are at risk of developing toxoplasma encephalitis (TE). Standard therapy regimens (including sulfadiazine plus pyrimethamine) are hampered by severe side effects. While atovaquone has potent in vitro activity against Toxoplasma gondii, it is poorly absorbed after oral administration and shows poor therapeutic efficacy against TE. To overcome the low absorption of atovaquone, we prepared atovaquone nanosuspensions (ANSs) for intravenous (i.v.) administration. At concentrations higher than 1.0 μg/ml, ANS did not exert cytotoxicity and was as effective as free atovaquone (i.e., atovaquone suspended in medium) against T. gondii in freshly isolated peritoneal macrophages. In a new murine model of TE that closely mimics reactivated toxoplasmosis in immunocompromised hosts, using mice with a targeted mutation in the gene encoding the interferon consensus sequence binding protein, i.v.-administered ANS doses of 10.0 mg/kg of body weight protected the animals against development of TE and death. Atovaquone was detectable in the sera, brains, livers, and lungs of mice by high-performance liquid chromatography. Development of TE and mortality in mice treated with 1.0- or 0.1-mg/kg i.v. doses of ANS did not differ from that in mice treated orally with 100 mg of atovaquone/kg. In conclusion, i.v. ANSs may prove to be an effective treatment alternative for patients with TE.